2010
DOI: 10.1111/j.1365-2966.2010.17452.x
|View full text |Cite
|
Sign up to set email alerts
|

Are brightest halo galaxies central galaxies?

Abstract: It is generally assumed that the central galaxy in a dark matter halo, that is the galaxy with the lowest specific potential energy, is also the brightest halo galaxy (BHG), and that it resides at rest at the centre of the dark matter potential well. This central galaxy paradigm (CGP) is an essential assumption made in various fields of astronomical research. In this paper, we test the validity of the CGP using a large galaxy group catalogue constructed from the Sloan Digital Sky Survey. For each group, we com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
270
5
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(306 citation statements)
references
References 120 publications
30
270
5
1
Order By: Relevance
“…We also derive P BNC , the probability that the brightest cluster member is not the central galaxy. We find P BNC ≈ 20 − 30% which is a factor of ∼ 2 lower than the value found by Skibba et al (2011). Finally, we study the radial offsets of bright non-central LRGs from cluster centers and show that bright noncentral LRGs follow a different radial distribution compared to red cluster members, which follow a Navarro-Frank-White profile.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…We also derive P BNC , the probability that the brightest cluster member is not the central galaxy. We find P BNC ≈ 20 − 30% which is a factor of ∼ 2 lower than the value found by Skibba et al (2011). Finally, we study the radial offsets of bright non-central LRGs from cluster centers and show that bright noncentral LRGs follow a different radial distribution compared to red cluster members, which follow a Navarro-Frank-White profile.…”
Section: Introductionmentioning
confidence: 78%
“…Furthermore, it is usually assumed that BCGs are central galaxies (van den Bosch et al 2004;Weinmann et al 2006;Budzynski et al 2012). However, recent results suggest that the central galaxy is not the BCG in all clusters (van den Bosch et al 2005;Coziol et al 2009;Sanderson et al 2009;Skibba et al 2011;Einasto et al 2011Einasto et al , 2012Sehgal et al 2013;Lauer et al 2014). For example, by analyzing differences between the velocities and positions of BCGs relative to other cluster members, Skibba et al (2011) found that 40% of BCGs may in fact be satellite galaxies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is often a large offset between the true mass centre and the bright centre galaxy (e.g. Sanderson et al 2009;Skibba et al 2011). Moreover, other aspects can also cause systematics, such as the irregular shape, massive substructures and multiple critical curves.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…This galaxy is assumed to be the central galaxy and at rest relative to the group. Although the most massive group galaxies can be offset and not at rest with the group (e.g., Skibba et al 2011), we prefer this definition to the barycentre, since the galaxy number density profiles in clusters are known to be less cuspy when clusters are centered on their barycentres (Beers & Tonry 1986), and indeed most analyses adopt the central galaxy as the position of the group centre.…”
Section: Basic Group Findermentioning
confidence: 99%